2016
DOI: 10.7863/ultra.15.09019
|View full text |Cite
|
Sign up to set email alerts
|

Value of Ultrasound Elastography in the Differential Diagnosis of Cervical Lymph Nodes

Abstract: Ultrasound elastography adds no additional value to combined B-mode and color Doppler sonography for differentiation of benign and malignant cervical lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 20 publications
3
33
1
Order By: Relevance
“…In a study by Acu et al . [ 25 ], the strain index from ultrasound images classified benign and malignant cervical LNs with a sensitivity, specificity, and accuracy of 71.6%, 76.5%, and 75.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Acu et al . [ 25 ], the strain index from ultrasound images classified benign and malignant cervical LNs with a sensitivity, specificity, and accuracy of 71.6%, 76.5%, and 75.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Many prospective and retrospective studies concerning the strain elastography of cervical lymph nodes have been conducted. 3 4 12 13 14 15 Lyshchik et al 12 indicated that sonoelastography had a high accuracy for differentiating benign and metastatic cervical lymph nodes in patients suspected of having thyroid or hypopharyngeal cancer. Alam et al 13 showed that the combination of highly specific elastography with highly sensitive conventional B-mode sonography had the potential to further improve the diagnosis of metastatic enlarged cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, Lo et al 15 showed that qualitative real-time elastography offered no additional value over conventional ultrasound in predicting malignancy in cervical lymph nodes. Acu et al 3 reported that ultrasound elastography added no additional value to combined B-mode and color Doppler sonography for differentiating between benign and malignant cervical lymph nodes. Shingaki et al 11 showed that intraoral strain elastography could be an alternative noninvasive method for diagnosing tongue carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Strain elastography with ultrasonography is a relatively new imaging technique that has been found to be effective for the differential diagnosis of cervical lymph node metastasis. 2 3 In recent years, strain elastography of the tongue has been found to be effective for differentiating healthy tissues and squamous cell carcinoma (SCC). 4 5 …”
Section: Introductionmentioning
confidence: 99%